The relationship between the season of birth and early‐onset food allergies in children. Issue 7 (13th August 2015) - Tanaka, Kajiyo; Matsui, Teruaki; Sato, Arisa; Sasaki, Kemal; Nakata, Joon; Nakagawa, Tomoko; Sugiura, Shiro; Kando, Naoyuki; Nishiyama, Takeshi; Kojima, Seiji; Ito, Komei
Abstract Background This study examined the relationship between the season of birth (SoB) and other factors with the development of FA. Methods A multicenter, cross‐sectional pilot study recruited 1197 patients with FA. The main study recruited 440 incident cases (FA group) definitively diagnosed as FA at 0–1 year of age. In both studies, the frequency of autumn–winter births (AWBs) in FA patients was compared to the regional control population. In the main study, we analyzed the differences in the SoB and other factors between patients in the FA group and those in the non‐FA group (n = 332) in allergy clinics. Results The pilot study showed that the frequency of AWB (57.6%) in the FA patients was significantly higher than that of the regional control population (50.4%, OR, 1.34; p < 0.001). The main study also showed the dominance of AWB (62.7%) in the FA group in comparison with that in the regional control population (50.2%, OR, 1.70; p < 0.001). Preterm birth (OR, 0.43; p = 0.027) and the presence of two or more elder siblings (OR, 0.27; p = 0.012) were significantly associated with a lower frequency of FA than those of non‐FA. AWB (RR, 1.21; p = 0.020) and preterm birth (RR, 0.55; p = 0.017) were significantly associated with a number of trigger foods. The SoB effect was observed in FA patients irrespective of the presence of infantile eczema. Conclusions AWB was predominant in the patients with newly diagnosed food allergies.